ChemInform Abstract: Efficient Preparation of Biologically Important 1, 2‐Amino Alcohols. Issue 21 (2nd May 2013) - Gupta, Pankaj; Rouf, Abdul; Shah, Bhahwal A.; Mukherjee, Debaraj; Taneja, Subhash C.
Abstract An efficient three‐step methodology for the formation of 1, 2‐amino alcohols (V) is developed which involves a rapid coupling between bromoketones and potassium phthalimide, subsequent selective reduction and finally an efficient removal step of the phthalimido protection group.